(untitled) (Ius Novum, 2023)
The focus of this article is the regulation of Article 62(1) of the Act on Counteracting Drug Addiction of 29 July 2005, often referred to in literature as ‘possession for personal use’. The fundamental issue related to the subject matter pertains to the definition of the legal good in Art. 62(1) of the Act. Contrary to initial impressions, identifying this interest is neither simple nor unequivocal, as there may be doubts over whether such a good protected by law exists and, if so, whether it should be protected under criminal law. The article also explores the correlation of this legal good and the need to protect it with other legal goods protected by the Constitution (e.g. individual freedom). Additionally, the article also examines the significance of the consent of a holder of a given good for the exclusion of unlawfulness or the absence of any attack on the legal good. Behaviour undertaken with the consent of the holder, allegedly “violating” the legal good, is after all, an act that conforms to the norm from the outset, and therefore does not involve any element of unlawfulness. As such, it does not constitute a criminal act. There are doubts whether in the case of possession and use of drugs, there is a threat to the legal good or whether such conduct is lawful from the very beginning, given the consumer’s consent. The article critiques the existing criminal law regulations, and its key argument is the thesis that drug addiction is an issue of exclusively medical and social concern, rather than one of criminal law.